Photodynamic inactivation of planktonic cultures and biofilms of Candida albicans mediated by aluminum-chloride-phthalocyanine entrapped in nanoemulsions - Ribeiro, Ana Paula Dias [UNESP]; Andrade, Mariana Carvalho [UNESP]; De Fátima Da Silva, Julhiany [UNESP]; Jorge, Janaina Habib [UNESP]; Primo, Fernando Lucas; Tedesco, Antonio Cláudio; Pavarina, Ana Claudia [UNESP] (Wiley, 2013)
New drug delivery systems, such as nanoemulsions (NE), have been developed to allow the use of hydrophobic drugs on the antimicrobial photodynamic therapy. This study evaluated the photodynamic potential of aluminum-chloride- phthalocyanine (ClAlPc) entrapped in cationic and anionic NE to inactivate Candida albicans planktonic cultures and biofilm compared with free ClAlPc. Fungal suspensions were treated with different delivery systems containing ClAlPc and light emitting diode. For planktonic suspensions, colonies were counted and cell metabolism was evaluated by XTT assay. Flow cytometry evaluated cell membrane damage. For biofilms, the metabolic activity was evaluated by XTT and ClAlPc distribution through biofilms was analyzed by confocal laser scanning microscopy (CLSM). Fungal viability was dependent on the delivery system, superficial charge and light dose. Free ClAlPc caused photokilling of the yeast when combined with 100 J cm-2. Cationic NE-ClAlPc reduced significantly both colony counts and cell metabolism (P < 0.05). In addition, cationic NE-ClAlPc and free ClAlPc caused significant damage to the cell membrane (P < 0.05). For the biofilms, cationic NE-ClAlPc reduced cell metabolism by 70%. Anionic NE-ClAlPc did not present antifungal activity. CLSM showed different accumulation on biofilms between the delivery systems. Although NE system showed a lower activity for planktonic culture, cationic NE-ClAlPc showed better results for Candida biofilms. Candida albicans biofilm overview after 30 min of contact with free ClAlPc. This study presents the photodynamic potential of aluminum-chloride-phthalocyanine (ClAlPc) entrapped in cationic and anionic nanoemulsions (NE) to inactivate C. albicans planktonic cultures and biofilm comparing with free ClAlPc. The photodynamic effect was dependent on the delivery system, superficial charge and light dose. Cationic NE-ClAlPc and free ClAlPc caused significant reduction in colony counts, cell metabolism and damage to the cell membrane (P < 0.05). However, only the free ClAlPc was able to cause photokilling of the yeast. The anionic NE-ClAlPc did not present antifungal activity. Although NE system showed a lower activity for planktonic culture, cationic NE-ClAlPc showed better results for Candida biofilms. © 2012 Wiley Periodicals, Inc. Photochemistry and Photobiology © 2012 The American Society of Photobiology.
Keywords: Candida; Candida albicans